Patient‐centred dietetic care from the perspectives of older malnourished patients. Issue 5 (22nd May 2017) - Hazzard, E.; Barone, L.; Mason, M.; Lambert, K.; McMahon, A.
Abstract: Background: Governing organisations for health services currently recommend a patient‐centred (PC) approach to practice for all health professions, including dietetics. For the vulnerable older malnourished patient, this approach needs to be prioritised to improve outcomes. The paucity of patient experience data likely limits evidence‐based, patient‐centred care (PCC) from being implemented effectively. The present study aimed to identify quality indicators of dietetic services from the perspectives of older malnourished patients to inform evidence‐based PC dietetic care. Methods: Surveys were completed by a sample of 28 females and 28 males (mean age 81 years) who had been seen by a dietitian for malnutrition assessment. In‐depth, face‐to‐face, semi‐structured interviews were undertaken with a sub‐sample of four females and six males (mean age 81 years). Interviews were transcribed verbatim. Thematic analysis of transcripts and open‐ended survey responses was conducted to determine patient‐identified quality indicators. Results: Three structure indicators (continuity of care through regular contact and post‐discharge dietetic follow‐up; interdisciplinary coordination and collaboration; and high‐quality hospital food services), five process indicators (addressing a patient's primary medical concern; involving the patient's family; providing clear and simple dietetic information; providing expert dietary knowledge; utilising interpersonal communication skills) and three outcome indicators (improvement in health status; improvement or maintenance of independence; weight gain) were identified. The experiences of older malnourished patients with dietetic services, as described in the present study, reinforce the importance of ensuring high‐quality and tailored dietetic care as a key element of PC dietetic services. Conclusions: The quality indicators of dietetic services identified in the present study may facilitate dietitians to provide evidence‐based PCC for older malnourished patients.